Natural philosophy in Gulliver’s Travels: an epistemological critique - Davis Perry, Lori A. (Studia Anglica Posnaniensia, 2025)
In Gulliver’s Travels, Swift challenges the epistemological authority of the experimental scientific models promoted by the Royal Society. Gulliver functions as an imaginative, literary embodiment of epistemological claims, a living thought experiment, that exposes the weaknesses of the Society’s assumptions. Swift’s satire thus offers a sceptical epistemological critique to some of the most important scientific claims of the eighteenth century. This paper argues that Swift challenges the Royal Society’s methods of knowledge-making: first, Gulliver’s troubled observations bely his representation as Boyle’s ideal, modest observer; second, the Professor and his students in the Academy of Lagado undercut the social construction of facts and scientific knowledge as promoted by the Royal Society’s public experiments and written reports. Swift’s satire thus operates as a serious discursive move within the larger conversation about the truth claims of the new philosophy, and Swift situates himself not as an acolyte but as an intellectual partner in the dance between the story of science and satire.